The Potential of Rice Straw for Ruminant Production in The Tropics-Effect of Variety, Urea Treatment and Supplementation on Compensatory Growth of Fat-Tail Sheep After a Period of Feed-Quality Restriction - S. Chuzaemi; J. van Bruchem; A. Hadayati; Soebarinoto (Soebarinoto); S. Prawirokusumo (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy